Otimização de vigas mistas aço-concreto com perfis "I" soldados - Tormen, Andréia Fátima (2019)
Optimized design of structures requires reduction of cost and also the fulfillment of technical specifications of security. Structural optimization methods has been inserted in this context in order to make faster and allow the obtainment of possible and satisfactory solutions, which can provide more economical structures. However, besides the economic gain, the use of these optimization techniques in a structural project allows to consider the factors related to the environmental impacts from process, as well as in the post-project and structural design processes. In this sense, this work proposed a mathematical model for the optimization of steel-concrete composite beams in order to minimize the monetary cost with materials and environmental impact, using the Harmony Search optimization method, which is a metaheuristic method based in analogy to the process of obtaining the best musical harmony. The model has been based on improvements in the structure of the Harmony Search optimization method, proposed by Medeiros and Kripka (2017). The discrete variables were the dimensions of the steel sections and the thickness of the cooperating slab of the steel concrete composite beam. The analyzes followed the recommendations of Brazilian standards for steel composite structures (ABNT NBR 8800/2008) and for welded steel I profiles (ABNT NBR 5884/2013). The proposed model has been implemented in the Fortran programming language. In order to prove the effectiveness and applicability of the proposed model, as well as the Harmony Search method, a series of analyzes has been carried out with different configurations of steel-concrete composite beam, aiming to provide guidelines that make the use of these systems more rationalized. In general, the Harmony Search optimization method was efficient in the search for optimized solutions, as well as important considerations on the optimization of the monetary costs with materials and environmental costs of steel-concrete composite beams were obtained from the examples developed.